2020
DOI: 10.1111/sji.12981
|View full text |Cite
|
Sign up to set email alerts
|

T cell immunoglobulin and mucin domain protein 3 inhibits glycolysis in RAW 264.7 macrophages through Hexokinase 2

Abstract: T cell immunoglobulin and mucin domain‐3 (Tim‐3), an immune checkpoint molecule, plays critical roles in maintaining innate immune homeostasis; however, the mechanisms underlying these roles remain to be determined. Here, we determined that Tim‐3 controls glycolysis in macrophages and thus contributes to phenotype shifting. Tim‐3 signal blockade significantly increases lactate production by macrophages, but does not influence cell proliferation or apoptosis. Tim‐3 attenuates glucose uptake by inhibiting hexoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
(121 reference statements)
0
8
1
Order By: Relevance
“…When knocked down the HK2 expression using HK2 siRNA, the inhibition is reversed. 69 Synthesis of novel andrographolide Beckmann rearrangement derivatives can inhibit the activity of HK2, thereby reducing the release of IL-1β in RAW264.7 cells induced by LPS. 51 In summary, HK contributes to NLRP3 inflammasome priming and activation; the agents that inhibit HK expression or dissociating from the mitochondrial membrane may prevent NLRP3 inflammasome-mediated inflammation.…”
Section: Hkmentioning
confidence: 99%
“…When knocked down the HK2 expression using HK2 siRNA, the inhibition is reversed. 69 Synthesis of novel andrographolide Beckmann rearrangement derivatives can inhibit the activity of HK2, thereby reducing the release of IL-1β in RAW264.7 cells induced by LPS. 51 In summary, HK contributes to NLRP3 inflammasome priming and activation; the agents that inhibit HK expression or dissociating from the mitochondrial membrane may prevent NLRP3 inflammasome-mediated inflammation.…”
Section: Hkmentioning
confidence: 99%
“…The rapidity of the response to the drug suggests that the underlying mechanism is likely transcription-independent and thus different from the transcriptomic or epigenetic immune-subversions strategies we previously reported (Lecoeur et al, 2022; Lecoeur et al, 2020). For example, the inhibition of LIMs glycolytic activity may be linked to the increased expression of havcr2 , an immune regulator that inhibits Mφ glycolysis through Hexokinase 2 (Zhang et al, 2021), which can be inhibited by intermediate metabolites such as Glucose-6-P. In addition, other metabolites such as ATP or citrate can inhibit additional steps in the glycolytic pathway, acting on phosphofructokinase 1 and pyruvate kinase 1 (Escoll and Buchrieser, 2018; Porporato et al, 2011) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, Strauss et al showed the connection between myeloid cell’s PD-1 expression and metabolic reprogramming of the myeloid progenitor cells [ 160 ], where PD-1-deficient myeloid cells induced increased metabolic intermediates of glycolysis, the pentose phosphate pathway, and the TCA cycle, but, most prominently, elevated the level of cholesterol, resulting in an increased T cell effector function [ 160 ]. Tim3, an immune checkpoint molecule, controls the glycolytic metabolism and lactate production by macrophage cells [ 161 , 162 ]. However, some TAM subsets rely on PD-L1/PD-1 signaling to stimulate glycolysis.…”
Section: Tam Metabolism As a Target For Immunotherapymentioning
confidence: 99%